Reaching the Voters: Parties’ Use of Google Ads in the 2021 German Federal Election - Fitzpatrick, Jasmin (2024)
Election campaigns during the pandemic showcased the increased use of costly digital campaigning by parties. While many studies focus on the use of Facebook, X (formerly Twitter), and other social networking sites during elections, parties’ use of Google Ads remains widely unstudied. This is surprising given that parties spend a substantial proportion of their budget on Google Ads and Google reports on this spending and other details of the ads in its Transparency Report. Based on the equalisation vs. normalisation thesis, we identify party factors (size, age, government/opposition status, and electoral strongholds) that affect parties’ use of this instrument to a different degree in their campaigns. We aim to highlight parties’ use of Google Ads during the campaigns for the 2021 German Bundestag election, relying on the official data provided via Google’s Ad Library. We discuss both empirical work on the factors that determine the use of Google Ads and conceptual work on the merit and perils of such ads in democratic elections, and we present descriptive and exploratory findings of our deep dive into the archive of Google Ads.